Game Strategies as a Principle of Creating Supertext Unity in Work of B. Akunin - A. B. Borunov (Научный диалог, 2023)
The article is devoted to the strategies for creating a prosaic super-cycle by Boris Akunin by referring to the technique of the game as a through cycle-forming principle. The relevance of the proposed analysis is due to the fact that the potential for creating principles for creating supertextual unity requires additional research in Russian literary criticism, since in modern literature a number of authors resort to this particular model of arranging their works (in addition to Akunin, these are, for example, Pelevin, Rubina, Vodolazkin, etc.). The novelty of the study is due to the research of how the works of the “Fandorin corpus” are combined into a supertext integrity due to a number of game tactics, including the tactics of an enigmatic-game dialogue with the reader. The classic canon of the detective, set by 19th-century authors, involves a game with the reader based on the calculation of the criminal, and this game is hermetic. Akunin, explicitly referring to the 19th century in the annotations to the New Detective series, opens the game system in the text of the detective story, offering the reader to enter an interactive quest at will. The same principle is used in other works of the “Fandorin corpus”.